Home-based family involvement and academic achievement: a case study in primary education. Issue 3 (27th May 2018) - Tárraga García, Verónica; García Fernández, Beatriz; Ruiz-Gallardo, José Reyes
Abstract: Does home-based family involvement influence academic performance? To answer this question, a case study research was carried out with 96 children from all six levels of primary education at a public school, and their families. Data regarding home-based family involvement were collected using a questionnaire. Academic achievement was measured from school marks. The results reveal that, apart from two of the factors considered, home–family involvement as a whole is not significantly related to academic achievement. These two factors are access to informal education resources and parents' employment. Family involvement related to the access of children to informal education resources is significantly related to a better academic achievement. Those students with both parents working perform best, and those with none working, worst. Although gender does not appear to significantly influence academic achievement and family involvement, the results show that girls attain better school performance and receive more family attention than boys.